O10.1 Age Specific Round 1 Results of a Cervical Cancer Screening Trial: HPV FOCAL. (13th July 2013) - Ogilvie, G; Krajden, M; Ehlen, T; Martin, R; Smith, L; Peacock, S; Stuart, G C E; Franco, E L; Coldman, A J
Abstract : Background: HPV FOCAL Study is a randomised trial evaluating the efficacy of high risk-HPV DNA (hr-HPV) testing, with Liquid Based Cytology (LBC) triage testing of hr-HPV positives, compared to LBC testing alone (with triage hr-HPV testing for ASCUS positives) in an organised screening programme. Round 1 age specific results comparing differences in screen detection rates between women < 35 yrs vs ≥ 35 yrs are presented. Methods: Between January 2008 and May 2012, 25, 243 consented women aged 25 to 65 were randomised to receive either: primary hr-HPV testing (HPV arms) or primary LBC testing (Control arm). Samples obtained with ThinPrep ® LBC. HPV testing performed with Qiagen Hybrid Capture 2 ® High-Risk HPV DNA Test. Results: Data is presented for 21, 985 participants enrolled as of July 1, 2011 who had completed Round 1 follow-up procedures by February 20, 2012. Overall, detection rates for CIN3+ were not statistically different between the HPV arm (7.8/1000; 95% CI: 6.1, 9.6) and the control arm (4.9/1000; 95% CI: 3.3, 6.5) when women of all ages were evaluated. In women ≥ 35yrs, the overall detection rate for CIN2+ and CIN3+ were both significantly higher in the HPV arm compared to the control arm (CIN2+: 9.9/1000 vs. 5.1/1000 respectively)(CIN3+: 4.4/1000 vs. 2.0/1000 respectively). For women < 35 yrs, HPV testing detected more CIN2+ and CIN3+ than LBC, but this did not achieve statistical significance. Overall, colposcopy referrals were higher in the HPV testing arm vs. control arm (59.1/1000, vs. 31.5/1000). HPV testing in < 35 yrs referred significantly more women to colposcopy than cytology (153.2/1000 vs. 73.3/1000). Conclusion: HPV screening with cytology triage detects significantly more CIN2+ lesions in women ≥ 35 years than LBC alone in the first round of screening. In women < 35, there was no difference in detection rates, but overall, HPV primary screening resulted in higher colposcopy rates.